Mobilization of Private Finance 2019 - MDB Task Force on Mobilization (Washington, DC, 2021)
This reporting year, Multilateral Development Banks (MDBs) continued to operate in a challenging investment environment - total investment flows declined by 6 percent worldwide in 2019 - and that environment promises to become even more challenging in 2020 and 2021 with the Coronavirus disease 2019 (COVID-19) pandemic, which calls for close MDB cooperation on mobilization of private investments. Private investment is critical for development, and MDBs’ research shows that greater mobilization is consistent with greater reductions in poverty and improvements in living standards, and MDBs remain resolute in their commitment to increase these flows. In this context, MDBs are committed to exploring new ideas and insights in mobilization, some of which are highlighted in the market trend essays in this report. The joint report documents that MDBs are significant financing partners in efforts to mobilize private capital toward emerging markets to help countries achieve the sustainable development goals (SDGs) and that MDBs will continue to play this important role during the COVID-19 pandemic and beyond.